Use of pesticides and its residue on vegetable crops in Nepal (Journal of Agriculture and Environment, 2015)
Farmer field survey and lab residue analysis studies were carried out to examine the use of pesticide in vegetable fields and its potential effects on human health and environment. Field information were collected using semi-structured questionnaires face to face interview with 200 farmers from three districts (Bara, Dhading and Kavre) of central region of Nepal. The recent study showed that the use of chemical pesticides in Nepal is 0.396Kg a.i./ha. The farmers' field survey showed that 72 percent of the farmers paid attention on acquiring information about the effectiveness of pesticide to control the target pests. While 65 percent of the farmers noticed the expiry date of pesticides, and only a few farmers considered the adverse effects of pesticide on human health and environment. The result showed that majority of them (51.5%) kept the remaining pesticides in their house freely, whereas 23.5 percent farmers destroyed the remaining pesticides; either buried or burnt. It was also found that 22.5 percent of farmers did not care and threw the remaining pesticides outside the house and in the fields. Residues analysis of 75 samples of 13 vegetables indicated that 58%t of the vegetable samples contained no detectable level (NDL) of the monitored pesticides, 38% samples resulted in trace level of the pesticides residue or below the minimum residue level (MRL), while 4% samples showed above MRL (EU Standard). Present study revealed ample scope for improvement on pesticide use and exposure, for which there is need of strong policy implementation, strengthening training, extension services and various awareness programs to farmers and agro-vets for judicious use of pesticides, health safety and environment protection.